2015
DOI: 10.1167/15.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual learning improves neural processing in myopic vision

Abstract: Visual performance is jointly determined by the quality of optical transmission of the eye and neural processing in the visual system. An open question is: Can effects of optical defects be compensated by perceptual learning in neural processing? To address this question, we conducted a perceptual learning study on 23 observers with myopic vision, targeting high frequency deficits by training them in a monocular grating detection task in the non-dominant eye near their individual cutoff spatial frequencies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…Thus, our results may also suggest that the initial VA had a positive effect on visual improvement, which is opposite to previous studies. For example, Yan et al (2015) found greater acuity improvement for observers with worse initial VA. Yehezkel et al (2016) also found that subjects with more advanced presbyopia and thus poorer initial VA showed the greatest improvement in VA. Even so, there were at least two differences between these previous studies and this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our results may also suggest that the initial VA had a positive effect on visual improvement, which is opposite to previous studies. For example, Yan et al (2015) found greater acuity improvement for observers with worse initial VA. Yehezkel et al (2016) also found that subjects with more advanced presbyopia and thus poorer initial VA showed the greatest improvement in VA. Even so, there were at least two differences between these previous studies and this study.…”
Section: Discussionmentioning
confidence: 99%
“…First, the initial vision and age differed. Yan et al (2015) recruited myopic adult observers; Zhou et al (2012) recruited presbyopic adults; and the present study recruited adolescent observers with normal or close to normal vision. Second, the incentive conditions were different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTM analysis of the CSFs in both the zero and high external-noise conditions (Chen et al, 2014 ; Yan et al, 2015 ) identified a mixture of an internal noise-reduction mechanism (to 46.89% ± 3.49% and 64.87% ± 4.37% of the pretraining levels in the high- and no-reward conditions, respectively, averaged across spatial frequencies; A a in Figure 2D ) and an external noise-exclusion mechanism (to 83.45% ± 4.78% and 83.35% ± 3.86% of the pretraining levels in the high- and no-reward conditions, respectively, averaged across spatial frequencies; A f in Figure 2D ; see PTM fitting in Supplementary Information for details). High reward enhanced internal noise reduction, t (9) = −3.253, p = 0.010, but the magnitudes of external-noise exclusion were comparable in the two reward groups, t (9) = 0.015, p = 0.988.…”
Section: Experiments 2: High Reward Boosts Perceptual Learning Throughmentioning
confidence: 99%
“…The good news continues in the contribution by Yan et al (2015). Myopic patients improved contrast sensitivity and visual acuity through perceptual learning, mainly due to a reduction of internal noise.…”
Section: Clinical and Appliedmentioning
confidence: 99%